Paciente con Insuficiencia Respiratoria aguda más Incontinencia Urinaria ingresada en la Unidad de Cuidados Intensivos del Hospital General Babahoyo. - González Zalabarria, Darwin Orlando (2020)
The following clinical case is about a 68 year-old female patient who enters the Emergency area due to having respiratory difficulties of several days ago, insomnia at night, tiredness, also indicates that she has a loss of urine when she performs an activity, Even when I sneeze or when I cough and more at night, I arrive with her husband who indicates that his wife a few years ago smoked but not regularly. Due to the symptoms presented by the patient, urinary incontinence is suspected in addition to respiratory failure. Urinary incontinence such as respiratory failure are two very frequent complications within a hospital ward and sometimes it is unknown why they appear, this study was developed in order to obtain a deeper and clearer vision of what the problem of different factors that are associated with these acute conditions since both can be totally improved if it is treated on time or it can get worse if a specific treatment is followed for its speedy recovery. The objective of this case is to identify the epidemiological profile of patients diagnosed with urinary incontinence and respiratory failure. It is recommended that if there are any signs or symptoms, however mild it may be, it is necessary to go to the doctor as life-threatening complications can be caused by the simple fact that it is not diagnosed in time.